2005
DOI: 10.1007/s10549-004-1250-y
|View full text |Cite
|
Sign up to set email alerts
|

The 3020insC allele of NOD2 predisposes to early-onset breast cancer

Abstract: The NOD2 gene has been associated with susceptibility to Crohn's disease, and more recently with carcinoma of the colon as well. NOD2 is involved in the inflammatory response and the activation of the NFkB pathway. The range of cancer types associated with NOD2 has not been well studied. The 3020insC allele results in a truncated NOD2 protein and is present in approximately 7% of the population. We studied a possible association between the 3020insC allele of the NOD2 gene and breast cancer using 462 cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 12 publications
6
35
1
Order By: Relevance
“…In addition, Nod2 L1007fsinsC has been also associated with a growing number of malignant diseases, including early onset breast cancer [97], non-Hodgkin's lymphoma [98] and lung cancer [99]. The molecular mechanisms underlying these associations are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nod2 L1007fsinsC has been also associated with a growing number of malignant diseases, including early onset breast cancer [97], non-Hodgkin's lymphoma [98] and lung cancer [99]. The molecular mechanisms underlying these associations are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have reported that breast cancers in women with NOD2 mutations characteristically show foci of ductal carcinoma in situ [7].…”
Section: Discussionmentioning
confidence: 99%
“…Many pathways and genes have been implicated in the process of breast cancer development. These include BRCA1, BRCA2, CHEK2, CDKN2A (p16), NOD2, and NBS1 (Lubinski et al 2004;Debniak et al 2005;Gorski et al 2005;Huzarski et al 2005). Recently Zhu et al (2005) have analysed 15 breast cancer samples for mtDNA mutations.…”
Section: Breast Cancermentioning
confidence: 99%